CHARACTERISTICS AND ESSENCE OF FATWAS ON ISLAMIC ECONOMIC LAW IN INDONESIA - Witro, Doli; Hakim, Atang Abdul; Komaruddin, Koko (IAIN Tulungagung, 2021)
In Indonesia, one of the institutions authorized to issue fatwas is the Indonesian Ulama Council (MUI). MUI is an institution with the role and authority to issue fatwas for Indonesian citizens who are diverse in Islam which are not mentioned in the Al-Quran and Hadith. Although not all groups can accept the fatwa issued by the MUI or there are reaping criticism and controversy by some circles, the influence and role of the MUI fatwa are considerable in maintaining the peace of the Indonesian people. Departing from this, it is essential to see fatwas based on the characteristics and essence of fatwas on Islamic economic law. This paper is conducted in qualitative research. There are several approaches used in this paper, namely, the normative approach, the historical approach, and the political approach. This paper aims to reveal the characteristics and essence of fatwas on sharia economic law in Indonesia. The analysis results show that fatwas as a product of Islamic law are identical to fiqh and have inherent specific characteristization. In essence, a fatwa can become state law if there is recognition through competent state institutions.